Polyvinylidene Fluoride/Siloxane Nanofibrous Membranes for Long‐Term Continuous CO2‐Capture with Large Absorption‐Flux Enhancement. Issue 2 (5th November 2013) - Lin, Yi‐Feng; Wang, Chi‐Sen; Ko, Chia‐Chieh; Chen, Chien‐Hua; Chang, Kai‐Shiun; Tung, Kuo‐Lun; Lee, Kueir‐Rarn
Abstract In a CO2 membrane contactor system, CO2 passes through a hydrophobic porous membrane in the gas phase to contact the amine absorbent in the liquid phase. Consequently, additional CO2 gas is absorbed by amine absorbents. This study examines highly porous polyvinylidene fluoride (PVDF)/siloxane nanofibrous layers that are modified with hydrophobic fluoroalkylsilane (FAS) functional groups and successfully coated onto a macroporous Al2O3 membrane. The performance of these materials in a membrane contactor system for CO2 absorption is also investigated. Compared with pristine PVDF nanofibrous membranes, the PVDF/siloxane nanofibrous membranes exhibit greater solvent resistance and mechanical strength, making them more suitable for use in CO2 capture by the membrane contactor. The PVDF/siloxane nanofibrous layer in highly porous FAS‐modified membranes can prevent the wetting of the membrane by the amine absorbent; this extends the periods of continuous CO2 absorption and results in a high CO2 absorption flux with a minimum of 500 % enhancement over that of the uncoated membranes. This study suggests the potential use of an FAS‐modified PVDF/siloxane nanofibrous membrane in a membrane contactor system for CO2 absorption. The resulting hydrophobic membrane contactor also demonstrates the potential for large‐scale CO2 absorption during post‐combustion processes in power plants.